ECFA and Taiwan from the Perspective of International Law - Harryanto Aryodiguno (Problematika Hukum, 2018)
The Economic Cooperation Framework Agreement (ECFA) is an important milestone between the People's Republic of China and Taiwan; it is also the most critical achievement in improving the close cross-strait relations since President Ma Ying-Jeou took office in 2008. This article intends to use Guzman's rational choice theory of international law to analyze Taiwan's motivation for signing ECFA under East Asian regionalism, and to speculate whether Taiwan will abide by the relevant ECFA regulations. Signing the ECFA with China is mainly to break through the predicament of Taiwan's isolation under East Asian regionalism. As the first step in cooperation with East Asia, ECFA has a significant impact on Taiwan's credibility in East Asia. Regardless of whether there is a chance to cooperate with other East Asian countries in the future, if Taiwan gets off ECFA's relevant regulations, it will cause damage to Taiwan's credibility and may even obliterate the possibility of future cooperation with East Asian countries. Therefore, from the perspective of rational choice, in order to maintain Taiwan's good reputation and look forward to more cooperation possibilities in the future, complying with the relevant ECFA regulations is an obligation that Taiwan must fulfil.